Fig. 2 in Helminths Of Antarctic Rockcod Notothenia Coriiceps (Perciformes, Nototheniidae) From The Akademik Vernadsky Station Area (Argentine Islands, West Antarctica): New Data On The Parasite Community - Kuzmina, T. A.; Salganskij, O. O.; Lisitsyna, O. I.; Korol, E. M. (Zenodo, 2020)
Fig. 2. Average number of cysts of Corynosoma spp. in the body cavity of Notothenia coriiceps of five size groups. Published as part of Kuzmina, T. A., Salganskij, O. O., Lisitsyna, O. I. & Korol, E. M., 2020, Helminths Of Antarctic Rockcod Notothenia Coriiceps (Perciformes, Nototheniidae) From The Akademik Vernadsky Station Area (Argentine Islands, West Antarctica): New Data On The Parasite Community, pp. 99-110 in Zoodiversity 54 (2) on page 105, DOI:10.15407/zoo2020.02.099, http://zenodo.org/record/6455500